The variables x and y are related as `x+y= ln((e^x-e^y))`

`x+y= ln((e^x-e^y))`

=> `e^(x + y) = (e^x-e^y)`

=> `e^x*e^y = e^x - e^y`

Using implicit differentiation gives:

`e^x*e^y + e^x*e^y*(dy/dx) = e^x - e^y*(dy/dx)`

=> `(dy/dx)(e^x*e^y + e^y) = (e^x - e^x*e^y)`

=> `dy/dx = (e^x - e^x*e^y)/(e^x*e^y + e^y)`

**The required derivative **`dy/dx = (e^x - e^x*e^y)/(e^x*e^y + e^y)`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now